RANCANG BANGUN SISTEM TELEMETRI MULTI-CHANNEL UNTUK MONITORING SUHU DAN pH AIR MENGGUNAKAN JARINGAN WIFI - Ave Gierdo Alfaseno; Suryono Suryono (Youngster Physics Journal, 2015)
Water quality monitoring is very important to know condition of the water in a sector location. The water quality monitoring can anticipate a decrease of water quality by knowing water condition in real-time, in that way can be determined what factors that causes a decrease of water quality. The method used for water quality monitoring system in this paper is telemetry system (remote measurement) with the wifi network. Telemetry system choosed because its more efisien than the other, measurement can be remotely and in real-time. The test of water quality is bad or good can be known from the elements of test parameters. Parameters sample tested of this research are temperature and pH of the water. To respon physical symptom of changes in amount of water temperature used temperature sensor RTD (resistance temperature detector), and a pH sensor to respon condition of pH of the water. Both of the sensor's reading are converted from analog to digital (ADC) using microcontroller ATmega8535. Microcontroller ATmega8535 has USART feature (Universal Synchronous and Asynchronous Serial Receiver and Transmitter) as a serial communication mode. Serial communication technique in a multi-channel is done by using the RS-485 protocol as a communication link beetwen one unit to another until can connect 32 and using the RS-232 protocol to connect serial communication data to personal computer (PC). The data that has been obtained is sent to the monitoring station by a telemetry technique using the wifi network. Results of the data acquisition system RTD temperature sensor against a standard thermometer has a linear correlation coefficient R = 0.998. And the results of the data acquisition pH sensor against a standard pH meter has a linear correlation coefficient of R = 0.994. Results of the comparison between the data sent and received data has errors = 0 so that it can be ascertained no data is lost or gained.